In or out: the drug court dilemma - Fulkerson, Andrew (Criminology, criminal justice, law & society, 2016)
The drug court was developed as a response to the ineffectiveness of the traditional criminal justice response to addiction. Drug courts are limited in resources and placement opportunities for offenders. Accordingly, the issue of who is placed in the drug court program and why they are so placed is a critical factor in the effective utilization of drug court resources. This paper is a qualitative study of the perceptions of the drug court offenders related to their reasons for entering the program and whether this was the proper program for the needs of the offender and the community. Rehabilitation and avoiding prison are the primary reasons offered by participants for entering the drug court. The study suggests that drug court staff provide better information as to risks and rewards of drug court participation than do defense attorneys.